Georgia Architectural and Historic Properties Survey of Maddox Drug Store, 215 E. Screven St., Quitman, Brooks County, Ga., 1981 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Maddox Drug Store, 215 E. Screven St., Quitman, Brooks County, Ga., 1981. Two story rectangular building. Flat roof. Red brick. Cast iron cornice with brackets along parapet. Arched shuttered windows, with cast iron decorative pediments. Modernized street floor. Once had a balcony on 2nd story because there are doors on the 2nd floor at the east side of the building. Good condition. Drug store and offices were upstairs. Date of Construction: Prior to 1889. Built for use as a drug store by Sweat family. However, it was owned by the Avera's and used as Avera's Drug Store. The Avera's are one of Quitman's oldest and most prominent families. Mr. Maddox knows that the building was built between 1864 and 1889 because there was nothing there in 1864. All newspapers saved during this era were burned in a fire. Offices upstairs - (known) Dr. Donaldson, dentist. Dr. Dorough, a GP. Significant as part of a potential National Register district, a downtown commercial district of late 19th and early 20th century buildings.
Georgia Architectural and Historic Properties Survey of Maddox Drug Store, 215 E. Screven St., Quitman, Brooks County, Ga., 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 3200 DPI TIF. 300 DPI 4x6 JPG. 1012689 bytes.
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Quitman (Ga.); Brooks County (Ga.)